Numerical simulation of NACA4412 airfoil in pre-stall conditions. Issue 4 (30th November 2021) - Gleize, Vincent; Costes, Michel; Mary, Ivan
Abstract : Purpose: The purpose of this paper is to study turbulent flow separation at the airfoil trailing edge. This work aims to improve the knowledge of stall phenomenon by creating a QDNS database for the NACA412 airfoil. Design/methodology/approach: Quasi-DNS simulations of the NACA 4412 airfoil in pre-stall conditions have been completed. The Reynolds number based on airfoil chord and freestream velocity is equal to 0.35 million, and the freestream Mach number to 0.117. Transition is triggered on both surfaces for avoiding the occurrence of laminar separation bubbles and to ensure turbulent mixing in the wake. Four incidences have been considered, 5, 8 10 and 11 degrees. Findings: The results obtained show a reasonably good correlation of the present simulations with classical MSES airfoil simulations and with RANS computations, both in terms of pressure and skin-friction distribution, with an earlier and more extended flow separation in the QDNS. The database thus generated will be deeply analysed and enriched for larger incidences in the future. Originality/value: No experimental or HPC numerical database at reasonable Reynolds number exists in the literature. The current work is the first step in that direction.